CFD Design Performance Analysis for a High-Speed Propeller - Marian Ristea; Adrian Popa; Octavian-Narcis Volintiru (Applied Sciences)
It is recognized that boats which intervene in dangerous situations are characterized by high maneuverability, have good governance properties, and must be equipped with high-speed propellers. This paper proposes a computerized analysis, using Computational Fluid Dynamics modeling, of a high-speed propeller, in open water, from the perspective of velocity and pressure manifested on the propeller blades. The use of numerical methods allows to determine the thrust forces on the propellers, to highlight the areas in the propeller blade where the maximum and minimum pressures occur, to identify the cavitation zone and to visualize the degree of turbulence of the fluid flow on the propeller blades in rotational motion. The analysis proves to be an efficient procedure in determining the characteristics of a high-speed propeller before deciding its production/manufacture. The Shear Stress Transport method was used for fluid turbulence analysis and the “Thrust–Propeller RPM” diagram and “Torque–propeller RPM” diagram finalized this study, the mentioned diagrams being the most important in choosing an efficient propeller for a given boat.